Recognising the impact of traditional herbal medicine in managing cancer: The South African context - Sibusiso Xego; Learnmore Kambizi; Felix Nchu (AOSIS, 2021)
Background: The increasing prevalence of cancer is placing enormous pressure on health infrastructure globally. The ever rising cancer burden is not unique to South Africa but also to many low- and middle-income countries. Natural plant-based products have for long have been used traditionally for treating cancer. Approximately 7% - 48% of cancer diagnosed patients take herbal medicines post diagnosis. As herbal remedies are also used by South Africans, it is justifiable to investigate herbal medicinal use in the prompt detection as well as prevention of cancer. Aim: The aim of this article is to highlight the potential of South African medicinal plants to combat cancer. Method: This review summarises previous research (1991-2020) on the impact of traditional herbal medicine in managing cancer, and identifies the context between traditional and conventional medicines. Scientific databases such as Science Direct, PubMed, Research Gate, and Google Scholar were used to source primary and secondary data for this review. Results: The findings of the present study call for the integration of herbal medicines into the existing healthcare systems to encourage the open use of herbal medicines by cancer patients. In addition, this study revealed 19 medicinal plant species from 15 families that are commonly used for the management of cancer in South Africa's nine provinces. Conclusion: It is crucial to enhance collaboration between the existing healthcare systems and herbal traditional medicines in the provision of better care to patients at risk of, or who have been diagnosed with, cancer.